Tinjauan hukum terhadap kewajiban perizinan berusaha dalam praktik bisnis webinar berbayar - Chanan, Linggar Aditya (Maliki Interdisciplinary Journal, 2024)
In Indonesia, paid webinar business practices are discussed in this research. Webinars are one way to convey information online because the need for digital literacy is increasing. However, this phenomenon raises questions about whether paid webinar businesses require a business license. The purpose of this research is to analyze whether a paid webinar business requires a business license. The research method used is normative juridical legal research with a descriptive analytical approach. Data was obtained through literature study from various sources such as books, journals and scientific articles. The research results show that paid webinar businesses must have a business license in accordance with the law. Companies running webinars must have a business license, which can be obtained through an integrated electronic licensing system (OSS). This licensing process can be adjusted based on the risk level of business activities. Paid webinar business organizers must obtain a business license in accordance with applicable regulations. The licensing process can be carried out through the OSS system which makes it easier and faster to apply for business permits. Thus, this research provides a better understanding of the regulations that apply to paid webinar business practices in Indonesia.